2020
DOI: 10.18699/vj20.43-o
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis in the liver of male <em>db/db</em> mice during the development of obesity and type 2 diabetes

Abstract: Obesity and diabetes mellitus are known to lead to the development of metabolic syndrome and non-alcoholic fatty liver disease (NAFLD). The mechanisms of programmed cell death are actively involved in maintaining cellular homeostasis along development of NAFLD. Proteins of the BCL-2 family are key regulators of physiological and pathological apoptosis. Homozygous males of BKS.Cg-Dock7 m Lepr db /+/+/J mice (db/db mice) are charac terized by progressive obesity and the development of type 2 diabetes mellitus (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Type 2 Diabetic Liver Depending on MT. Hepatic apoptosis is regarded as the cytological basis for type 2 diabetes-induced liver damage [32]. In the present study, the hepatic apoptosis was first evaluated by TNUEL staining, which showed that the positive apoptotic liver cells, displayed in red, were hardly These results suggested endogenous MT mediated the prevention of zinc treatment on type 2 diabetes-induced hepatic apoptosis.…”
Section: Zinc Supplementation Induced Antiapoptotic Effect In Thementioning
confidence: 60%
See 1 more Smart Citation
“…Type 2 Diabetic Liver Depending on MT. Hepatic apoptosis is regarded as the cytological basis for type 2 diabetes-induced liver damage [32]. In the present study, the hepatic apoptosis was first evaluated by TNUEL staining, which showed that the positive apoptotic liver cells, displayed in red, were hardly These results suggested endogenous MT mediated the prevention of zinc treatment on type 2 diabetes-induced hepatic apoptosis.…”
Section: Zinc Supplementation Induced Antiapoptotic Effect In Thementioning
confidence: 60%
“…Hepatic apoptosis is regarded as the cytological basis for type 2 diabetes-induced liver damage [ 32 ]. In the present study, the hepatic apoptosis was first evaluated by TNUEL staining, which showed that the positive apoptotic liver cells, displayed in red, were hardly observed in the nondiabetic mice (Figures 7(a) and 7(b) ).…”
Section: Resultsmentioning
confidence: 99%
“…This results in a limitation of the model to fully mimic the complicated pathology development in DM-associated AS. Although previous studies have indicated that genetically obese rodent model db/db mice are more similar to T2DM [ 50 , 51 ], it is recognized, that STZ-induced ApoE −/− mice have shown more stable and recognized spontaneous atherosclerotic plaques [ 52 , 53 ]. Moreover, another limitation was that we constructed the HG-induced HUVECs to examine the function and mechanism of the miR-449a/CEACAM1 axis in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Leptin has demonstrated the ability to inhibit apoptosis and induce cell cycle by elevating Bcl-2 and cyclin D1 in leptin-receptor-deficient ( db/db ) mice [ 188 ]. Similarly, the Bcl-2 protein expression was elevated in db/db mice with diabetes [ 189 , 190 , 191 ], Which may be predisposed to develop lymphoma [ 192 ]. This adipokine also decreased the apoptosis of myocardial cells in rats via bcl-2 [ 193 ] and reduced the apoptosis of beta cells at physiological concentrations in vitro by maintaining or up-regulating bcl-2 expression, which could promote non-insulin-dependent diabetes mellitus [ 194 , 195 ].…”
Section: Leptin and Lymphomamentioning
confidence: 99%